The Effect Of Light Curing Intensity On Fluoride Release From Composite Resin - Manal A. Sultan (University of Mosul, College of Dentistry, 2009)
Aims: To find the effect of light cure intensity on polymerization of light cured composite resin(Tetric and Kerr composite resin). Which affects the amount of fluoride release from (light cure) composite resin. Materials and methods: Two types of light cure composite resins material (Tetric ceram and Kerr are used in this study, three groups of samples were made from each type of material used each group contain 10 samples which are cured by light cured device with different intensity of light cure.The first group of samples were cured by light the intensity of the light cure was 170 Mw/cm2. The second group of samples were cured by the intensity of 300 Mw/cm2 , third group of samples were cured at the intensity of 470 Mw/cm2. Results: The amount of fluoride released from all samples were determined in (milli volt)then convert to ppm(part per million).The amount of fluoride release in to deionized water from materials at the high intensity were less from the amount of the fluoride release from the materials that cured at low intensity. Conclusions: The amount of the fluoride from the light cured composite resins material which cured at the high intensity is less than the amount of the fluoride released from light cured composite resin at low intensity. Which means that the intensity of light cure will affecting the amount of the fluoride release from light cured composite resin materials.